Formação de mão de obra e déficits locais: o caso do IFSP campus Registro - Amaral, Guilherme Rodrigues do (2024)
The constant changes in the job market and the need for workforce training have a significant impact on the employability of Brazilians. In this way, this research aims to analyze, through a case study, how the educational training of labor is related to meeting local deficits in professional qualification, taking as a reference the socioeconomic context of Vale do Ribeira, specifically the city of Registro and higherlevel courses at the Federal Institute of São Paulo (IFSP), Registro campus. For the case study, qualitative data was collected through a socioeconomic questionnaire among Higher Education students from the Bachelor's Degree in Physics, Degree in Pedagogy and Bachelor's Degree in Production Engineering enrolled regularly from the first to the last semester. The results of the questionnaire indicate that 56% of respondents believe they will be able to obtain a paid internship in the area of study until the end of their degree, 74% believe that after completing the course they will be able to work in the area of training and 50% believe that there are job vacancies in the city of Registro and region in their study area. As for the Federal Institute of São Paulo (IFSP), Registro campus, it is evident that it is a democratic educational institution, aligned with current legislation, which promotes the training of professionals in order to meet the deficits in qualified labor at higher education levels in the city of Registro and the Vale do Ribeira region, considering and respecting the socioeconomic context in which the students are inserted. Finally, it is noteworthy that researches like this can contribute to a better understanding when installing new courses at the campus Registro of the Federal Institute of São Paulo and how much the local job market is capable of absorbing the trained workforce by the aforementioned institution given the demand for qualified professionals